STUDENTS’ PERCEPTION ON PEER CORRECTION IN ACADEMIC ENGLISH WRITING: A CASE STUDY IN A HIGHER EDUCATION - Tsuroyya, Chasna (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2020)
Peer correction has taken an important role in language teaching and learning as in contribution to motivate the performance of L2 learners in writing classroom. Peer correction encourages the development of autonomous learning due to teachers' review that took over-dependence thus lowered the students' initiative. However, the previous studies show that many teachers are still doubting the effectiveness of peer correction because of students' lack of knowledge and unable to assist other students. The current study investigated the writing performance of English L2 learners who either provided or received written peer correction in the context of academic writing tasks. Twenty participants enrolled and attended writing class in English Education Department in a state university in Surakarta. They were given a rubric to both reviews other students' writing tasks and receive peer feedback. In collecting data, questionnaires were collected after the writing projects. Results show the use of peer correction increased their writing motivation, self-regulated reflection, bidirectional communication, and deeper critical thinking. Thus, this study provide a clear finding of the efficiency of peer correction in improving students' academic writing and can be useful to be implemented in writing class for English learners